From Human Dignity to Natural Law : An Introduction - Berquist, Richard, 1932-; Berquist, Richard, 1932- (Book collections on Project MUSE., 2019)
"An exposition of human dignity as the foundation of moral order. From this starting point, the author derives the most important precepts of natural law from human dignity in a systematic way. Using the principle of human dignity, the author then develops natural law precepts to guide human behavior in various areas of life corresponding to the natural inclinations: life issues, sexual issues, political issues, and the contemplative life."